Improving safe blood availability at Baptist Hospital Mutengene (BHM). A cross-sectional study. - Rangellar, Ngam; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David (Student's Journal of Health Research Africa, 2025)
Background Blood transfusion saves millions of lives worldwide. In sub-Saharan Africa, it plays a key role in managing malaria-related anaemia in children. However, blood shortages remain a pressing issue and thus threaten healthcare systems reliant on transfusion, which is very common in Africa. This study aimed to improve the safe blood availability at Baptist Hospital Mutengene (BHM). Methodology Kotter’s and Lewin’s models guided the strategic change management approach, focusing on awareness campaigns, stakeholder engagement, and donor motivation. Educational sessions were conducted in hospitals, schools, and communities to increase participation. Incentives such as transport and feeding allowances were introduced to encourage voluntary non-remunerated blood donors (VNBD). Challenges encountered, including resistance to change, were managed through communication and active participation. Data was collected from donor records, staff reports, and voluntary donor feedback to assess progress. Results The initiative increased VNBD numbers from 70 in 2022 to 172 in 2024, with an ultimate goal of reaching 500 donors to ensure a stable blood supply. Donor deferrals due to medical ineligibility dropped from 12 per month to 2, improving blood safety. Regular blood drives yielded up to 30 units per event. The introduction of transport and feeding allowances encouraged donors, leading to a 10% increase in unscheduled donations. Health education efforts reduced socio-cultural barriers to donation. However, staffing shortages and limited blood bank storage space remained challenges. Conclusion This change initiative has improved blood donation at BHM through structured frameworks, stakeholder collaboration, and education campaigns, with sustained progress driven by teamwork, staff commitment, and administrative support despite challenges. Recommendation Further change is recommended in the area of blood management so that the available blood does not expire while patients are in dying need of it.